Spacecraft for well-being. Heritage, design, renewable sources for new lifestyles - Francesca Castanò; Luigi Maffei; Maria Dolores Morelli; Raffaella Marzocchi (Techne)
The paper describes the design method developed by the multidisciplinary research group comprising Heritage design, Ecodesign, Home Automation and Renewable Sources for the design of small demountable structures. The design process is characterised by attention to aspects related to health and well-being in order to orient contemporary habits through the use of spatial devices capable of distracting attention from the ways of continuous connection with the digital world. The “spacecraft”, small dismountable structures, characterised by home automation systems, renewable energy and sustainable materials, can constitute a “joyful spatial system” for manual making, listening to stories between different generations, cultivating cultures and reading books. They are designed to support the functions carried out in public buildings with specific uses, such as hospitals, social centres and retirement homes.